Leisure time physical activity in 9- to 11-year-old children born moderately preterm: a cohort study - M. Nordvall-Lassen; H. K. Hegaard; C. Obel; M. S. Lindhard; M. Hedegaard; T. B. Henriksen (BMC, 2018)
Abstract Background Physical activity is one of the best documented activities with impacts on health in children and adults. Children born preterm show reduced physical and psychosocial function compared to children born at term. This may influence their level of physical activity. Reports on moderately preterm children's physical activities during childhood are limited. Thus, the aim of this study was to compare the leisure time physical activity at age 9-11 years of moderately preterm children with that of children born at term. Methods Data from 4941 mother-child pairs from the Aarhus Birth Cohort (1989-91) were used. The cohort gathered clinical information, including gestational age at delivery. Information about parental socio-demographic and lifestyle factors was obtained from questionnaires completed during the second trimester of pregnancy. Information about children's physical activities was reported in a 9- to 11-year follow-up questionnaire completed by parents detailing how many times per week their child participated in sports activities outside of school, hours spent per week playing outside, and hours per week engaged in sedentary activities. Data were analysed using multiple logistic regression with the lowest activity group as a reference group. Results A total of 158 children (3.2%) were born moderately preterm, i.e., between 32 and 36 completed weeks. Children born moderately preterm participated in sports activities as often as their peers born at term; they also participated in frequent sports activities (≥ 4 times per week) as often as their peers. There were no differences in hours per week spent playing outside or in sedentary activities between the two groups. Conclusions Nine- to 11-year-old moderately preterm children participated in sports activities outside school to a similar extent as their peers and engaged in outdoor activities and sedentary activities for the same duration of time per week as their peers born at term.